POLICY NETWORK IN IMPLEMENTING THE ECOVILLAGE PROGRAM IN PALASARI VILLAGE, SUBANG REGENCY - Rizky Ilhami (INFOKUM, 2022)
This research aims to analyze and document the policy network involved in implementing the Ecovillage program in Palasari Village, Subang Regency. The ecovillage program aims to create villages/villages/sub-districts with a participatory and independent environmental culture, with the hope of having an impact on improving community welfare. The main focus of this research is to understand the structure and dynamics of the policy network that supports the implementation of the Ecovillage program and how interactions between stakeholders influence the success of the program. The research was conducted using a qualitative descriptive approach. Primary data collection was carried out by purposive sampling from relevant stakeholders. The instruments used for data collection were interviews, observation, document techniques and literature studies. The results of research conducted on the Ecovillage Program in Palasari Village show that the implementation of this program has had a positive impact on environmental preservation and sustainable development at the village level. This study found that through the implementation of an effective policy network between the West Java Provincial Government, the Palasari Village Government, and the local community, Palasari Village has succeeded in developing various environmental activities which include waste management, natural resource conservation, and community empowerment in independent environmental management.